PENGARUH FINANCIAL DISTRESS, GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN INSTITUTIONAL OWNERSHIP TERHADAP TAX AVOIDANCE - Sella Fitriana Fadhilah; Eny Kusumawati Kusumawati (ITB AAS INDONESIA, 2024)
Tax avoidance is one way of legally avoiding taxation by using the benefits of several loopholes in tax regulations in order to avoid paying tax, in other words carrying out transactions whose sole purpose is to avoid paying tax. This research aims to analyze the influence of financial distress, good corporate governance, leverage, and institutional ownership on tax avoidance in non-financial companies on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique used in this research was purposive sampling. A total of 314 companies have met the criteria as observation units. The analytical method used is multiple linear regression analysis. The research results provide empirical evidence that financial distress, managerial ownership, leverage, and institutional ownership effects tax avoidance. Meanwhile, independent commissioners has no effect on tax avoidance.